KADAR YODIUM AIR, EKSKRESI YODIUM URIN DAN GOITER DI DAERAH ENDEMIS DEFISIENSI YODIUM - Mutalazimah -; Setia Asyanti (Universitas Muhammadiyah Semarang, 2015)
Physical environmental factors contribute to human health, including the factor of iodine content of water in endemic areas related to urinary iodine excretion and goiter. Water iodine levels determine iodine intake comes from drinking water and determine the iodine content of foodstuffs produced from endemic areas. When iodine intake is too low, then the amount of iodine excreted in the urine is also low, it causes the thyroid gland is unable to maintain adequate hormone secretion, and goiter arise as compensation. This study aims to examine the relationship of water iodine levels, urinary iodine excretion (UIE) and goiter in women of childbearing age in endemic areas of iodine deficiency. This cross-sectional observational study, conducted in 115 women of childbearing age at Prambanan sub-district of Sleman, chosen at random. Water iodine levels and UIE were measured by acid digestion method, goiter measured by palpation method. The relationship between water iodine levels and UIE were analyzed with the Pearson correlation test, the relationship of water iodine levels and goiter were analyzed by Chi Square. The results showed that the average iodine content of water 4.95 mg / l ± 4.98 mg/l and median 8.00 mg/l (0-12 mg l), the average value of UIE included in the category more adequate (247.3 ± 158.5) mg/l and it also the median of 205 (0-774) mg/l. It was also found 13% sample have goitre. Statistical analysis result showed the relationship between water iodine levels and UIE (p = 0.014), while water iodine levels and goiter (p = 0.077). In conclusionthere was athere relationship between water iodine levels and UIE and there was no correlation between water iodine levels and goiter.Keywords: water iodine levels, UIE, goiter